0307 Is Poor Sleep Associated with Use of Multiple Benzodiazepine Receptor Agonists in Older Veterans?. (25th May 2022) - Ghadimi, Sara; Alessi, Cathy; Kelly, Monica; Martin, Jennifer; Moore, Alison; Grinberg, Austin; Zeidler, Michelle; Dzierzewski, Joseph; Mitchell, Michael; Guzman, Andrew; Armendariz, Jessica; Badr, Safwan; et al.
Abstract: Introduction: Benzodiazepine receptor agonists (BZAs) are often prescribed for insomnia in older adults. Polypharmacy increases risk of adverse events in this population in general, particularly when medications within the same class are prescribed. During an ongoing hypnotic deprescribing trial, we explored use of more than one BZA (multi-BZA use) and self-reported sleep quality among older adults. Methods: Telephone surveys were performed for recruitment to an ongoing BZA deprescribing trial. Participants aged ≥ 55 years who were prescribed at least one BZA (i.e., alprazolam, clonazepam, lorazepam, temazepam, or zolpidem) from a Department of Veterans Affairs pharmacy in Southern California were asked about their use of each BZA over the past 3 months for sleep (yes/no). Multi-BZA use was defined as using > 1 different BZA over the past 3 months. Self-reported sleep items included duration of sleep problems (<3, 3-12, or >12 months), sleep quality (very or fairly good, fairly or very bad), and sleep efficiency (mean total sleep time over time in bed). Analyses compared sleep variables between multi-BZA and non-multi-BZA users (Fisher's Exact or t-tests). Results: Among participants (N=359), 152 (42.3%) reported using zolpidem, 41 (11.4%) lorazepam, 39 (10.9%) alprazolam, 31 (8.6%) clonazepam, and 29 (8.1%) temazepam during the past 3 months. 35 (9.8%) participants reported taking more than one of these drugs. 93.9% reported their sleep problems were present for ≥3 months. 68.3% of participants reported their sleep was fairly/very bad, and mean sleep efficiency was 67.9 (SD 18.5). There were no significant differences between multi-BZA versus non-multi-BZA users in duration of sleep complaints (Fisher's Exact=1.0; p=.842), sleep quality (Fisher's Exact=0.70; p=0.56) or sleep efficiency (p=0.91). Conclusion: We found 1 in 10 older adults prescribed a BZA for sleep reported multi-BZA use over the past 3 months. Multi-BZA use was unrelated to duration of sleep complaints, sleep quality or sleep efficiency. Whether the use was simultaneous or staggered, these findings are concerning, given the elimination half-life of most of the BZAs and that polypharmacy, especially within medication class, may increase risk of adverse events (e.g., falls). Further research is needed to explore factors contributing to multi-BZA use. Support (If Any): NIA R01AG057929, VA IIR 17-234